Regulations For The Guardian's Investment Of The Minor's Money In Trade _ Comparative Jurisprudence Study_ (Damascus University Journal for legal sciences, 2024)
The research deals with the issue of the investment of the guardian of the money of the minor through trading it, and its importance and the existence of a difference in the ways of investment, and because money is one of the most important purposes of Islamic law, this issue needed to indicate the controls that the guardian must abide by while investing the money of the minor, dividing the research into three demands, the first of which included the analysis of the terms of research by indicating the meaning of the officer, minor, guardian and investment, and then moved to the statement of controls that the guardian must abide by in the following two demands, the first of which included the following two demands. On the investment controls of the minor's guardian
Keywords: Officer; Minor; Guardian; Investment